Peran Lembaga Amil Zakat, Infaq dan Shadaqah Muhammadiyah (Lazismu) Banjarnegara dalam Meningkatkan Perekonomian Kaum Dhuafa - Sri Apriliyani; Zaini Abdul Malik (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. The role of zakat is very important, for that the amil zakat institution is a mandate of responsibility in managing zakat. The purpose of this study was to determine, Firstly the Role of Zakat in Increasing Empowerment, Secondly the Role of the Amil Zakat Institution, Infaq and Sadaqah Muhammadiyah Banjarnegara in enhancing empowerment in carrying out its programs relating to the economic empowerment of the people, especially the poor. The type of data analysis used in this study is a qualitative descriptive analysis, with field research specifications. The results of this study indicate that the role of the Amil zakat, infaq and shadaqah institutions in improving the economy of the poor is to use productive zakat funds as a program in the form of venture capital distributed by the LAZISMU Banjarnegara. And there is a change in economic improvement mustahiq after getting productive zakat funds with the qharhul hasan contract (benevolent loans). Abstrak. Peran zakat sangat penting, untuk itu lembaga amil zakat merupakan amanah tanggung jawab dalam pengelolaan zakat. Tujuan penelitian ini adalah untuk mengetahui, Pertama Peran Zakat dalam peningkatan pemberdayaan, Kedua Peran Lembaga Amil Zakat, infaq dan Shadaqah Muhammadiyah Banjarnegara dalam peningkatan pemberdayaan melaksanakan programnya yang berkaitan dengan pemberdayaan ekonomi umat khususnya kaum dhuafa. Jenis analisa data yang digunakan dalam penelitian ini adalah analisis deskriptif kualitatif, dengan spesifikasi penelitian field research (penelitian lapangan). Hasil dari penelitian ini menunjukkan bahwa peran dari Lembaga Amil zakat, infaq dan shadaqah dalam meningkatkan perekonomian kaum dhuafa yaitu dengan memanfaatkan dana zakat produktif salah satu program dalam bentuk modal usaha yang disalurkan oleh pihak LAZISMU Banjarnegara. Dan adanya perubahan peningkatan ekonomi mustahiq setelah mendapatkan dana zakat produktif dengan akad qharhul hasan (pinjaman kebajikan).